Odpowiedź :
Odpowiedź:
a) -3x +4= - 5x -1
-3x+5x= -1 -4
2x = -5 /:2
x= - 5/2 = - 2 i 1/2
spr... -3*(-5/2) +4= - 5 *(-5/2)-1
15/2 +4= 25/2-1
7 i 1/2+4= 12 i 1/2-1
11 i 1/2= 11 i 1/2
L=P
b) - ( 4+a) = 2 (3-a)
-4 -a= 6-2a
-a + 2a= 6 +4
a= 10
spr. -4 - 10 = 6- 2*10
-14= 6-20
-14= - 14
L=P
c) 0,75 ( 2-3x) = - 6
3/4 ( 2-3x) = - 6
6/4 -9/4x= - 6
- 9/4x= - 6 - 6/4
-9/4 x= - 6 i6/4
- 2 i 1/4x= - 7 i 2/4 /:( - 9/4)
x= -30/4 : (-9/4)
x= -30/4 *(- 4/9)( skracamy 4 i 4 przez 4, oraz 30 i 9 przez 3)
x= 10/3= 3 i 1/3
spr.. 6/4 - 9/4* 10/3 = - 6 ( skracamy 9 i 3 przez 3, oraz 10 i 4 przez 2)
6/4 - 15/2= -6
1 i 2/4- 7 i 2/4= - 6
-6= - 6
L=P
d) -0,5 ( -x-6) = - x
0,5x + 3= -x
0,5 x +x= -3
1,5 x= - 3 /:( 1,5)
x= - 3 : 15/10= - 3 * 10/15( skracamy 15 i 3 przez 3)
x= - 2
spr... 0,5 * (-2) +3 =2
-1+3= 2
2=2
L=P
6/4-
Szczegółowe wyjaśnienie: